Serendipitous Metal‐Catalyzed H–H/Si–H Exchange. Issue 18 (22nd May 2014) - Nikonov, Georgii I.; Vyboishchikov, Sergei F.; Shirobokov, Oleg G.; Simionescu, Razvan
Abstract: Various metal complexes catalyze exchange between H2 and hydrosilanes. Catalyst screening suggests that the electron deficiency of the metal center is necessary for exchange, but silane and/or hydrogen addition or σ‐bond metathesis with the M–Si and M–H bonds are not required. Kinetic measurements for the system [(ArN=)Mo(PMe3 )3 (H)(SiH2 Ph)/H2 /H3 SiPh] (Ar = 2, 6‐ i Pr2 C6 H3 ) suggest that the reaction proceeds through activation of the silane. Abstract : Metal‐catalyzed exchange between H2 and hydrosilanes occurs under conditions in which neither H–Si or H–H addition to metal nor σ‐bond metathesis with the M–Si or M–H bonds take place, which suggests a novel way of activating dihydrogen.